TEMPORAL INFILTRATION CHARACTERISTICS OF SOIL UNDER DIFFERENT AGES OF ACACIA PLANTATION IN LUONG SON HEADWATER, HOA BINH, VIETNAM - Thi Thanh Hoa, Dang; Xuan Dung, Bui (Journal of Forestry Science and Technology, 2020)
To determine the temporal infiltration characteristics of soil under different ages of Acacia plantation forest in a headwater of Hoa Binh Province, Vietnam, the field experiment for infiltration measurement by double ring method was established at different vegetation cover conditions (including bare land after burning, 1-year-old Acacia plantation, 2-year-old Acacia plantation, 3-year-old Acacia plantation, 4-year-old Acacia plantation and 5-year-old Acacia plantation) from July to September 2019. Potential factors affecting on soil infiltration were determined, including soil physical and vegetation characteristics of Acacia plantation. The main findings included: (1) Temporal infiltration rate in different ages of Acacia plantation tend to be decreased with increasing of ages. Both initial and stable rate are increased from bare land (initial rate: 7.9mm/min; stable rate: 1.2mm/min) to 5-year-old of Acacia plantation (initial rate: 14.2mm/min; stable rate: 2.5mm/min); (2) Temporal infiltration rate has a strong relationship with soil physical characteristics and understory vegetation cover. Initial infiltration rate of soil has a strong relationship with understory vegetation (R=0.84), porosity (R=0.87) and soil moisture (R=-0.87), but do not have significant relationship with dry bulk density (R=-0.22). While stable rate has a strong relationship with understory vegetation (R=0.70), it has a moderate relationship with porosity (R=0.53), dry bulk density (R=-0.51) and soil moisture (R=-0.44); (3) The findings implied that infiltration rate under Acacia plantation forest has been higher than bare land after burning. It can be explained that the root and understory vegetation have important impacts on infiltration characteristics of soil.